2020
DOI: 10.3390/nu12051379
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors of Long-Term Dietary and Physical Activity Adherence among Chinese Adults with Overweight and Obesity in a Community-Based Lifestyle Modification Program: A Mixed-Method Study

Abstract: There is a paucity of research on factors influencing long-term adherence to lifestyle modification. We conducted a mixed-method study to explore the psychological factors of dietary and physical activity (PA) adherence among Chinese adults with overweight and obesity at 10 months after enrollment of a community-based lifestyle modification program in Hong Kong. We recruited Chinese adults newly enrolled in a culturally adapted lifestyle modification program and followed them for 10 months. For the quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…As less self-efficacy has been found in NAFLD patients than in other chronic liver diseases [28], this could be a critical factor in understanding the lack of motivation these patients have for their treatment. Many studies have found better performance of physical activity and diet by diabetic and obese patients who have high perceived self-efficacy [29][30][31][32]. Similar results were found by Zelber-Sagi et al in a study with 146 ultrasound-diagnosed NAFLD patients [33]; however, more evidence is necessary to confirm the importance of self-efficacy in these patients.…”
Section: Introductionsupporting
confidence: 61%
“…As less self-efficacy has been found in NAFLD patients than in other chronic liver diseases [28], this could be a critical factor in understanding the lack of motivation these patients have for their treatment. Many studies have found better performance of physical activity and diet by diabetic and obese patients who have high perceived self-efficacy [29][30][31][32]. Similar results were found by Zelber-Sagi et al in a study with 146 ultrasound-diagnosed NAFLD patients [33]; however, more evidence is necessary to confirm the importance of self-efficacy in these patients.…”
Section: Introductionsupporting
confidence: 61%
“…Fourteen studies exclusively at activity behaviors [37][38][39][40][41][42][43][44][45][46][47][48][49][50] with one reporting only facilitators [42] and one only barriers [46]. Eleven studies reported barriers and facilitators in mixed interventions [51][52][53][54][55][56][57][58][59][60][61].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the nonpositive perception was significant predictor of cognitive training participation in the previous report [5], whereas we observed its negative association with participation in several intervention domains. We could not identify other publications that included the study perception, but this concept has been suggested to be used as a surrogate for self-efficacy that has been previously connected to exercise participation [11,12], likewise has a positive attitude [6]. In addition, earlier study focusing on computer-based cognitive training in the FINGER found that positive expectations were associated with joining the programme [28].…”
Section: Discussionmentioning
confidence: 99%
“…Among psychosocial factors, depressive symptoms have been quite consistently associated with poorer participation in the lifestyle interventions [5][6][7][8], or with greater dropout [9], but they have not always hampered reaching beneficial lifestyle modifications [10]. Positive attitude and self-efficacy have been associated with higher adherence to exercise programmes [6,11,12].…”
Section: Introductionmentioning
confidence: 99%